Alleviating manoeuvres (sensory tricks) in cervical dystonia. Issue 8 (14th May 2014) - Patel, Neepa; Hanfelt, John; Marsh, Laura; Jankovic, Joseph
Abstract : Background: There is limited information on the phenomenology, clinical characteristics and pathophysiology of alleviating manoeuvres (AM), also called 'sensory tricks' in cervical dystonia (CD). Methods: Individual data, collected from 10 sites participating in the Dystonia Coalition (http://clinicaltrials.gov/show/NCT01373424 ), included description of localisation and phenomenology of AM collected by systematic review of standardised video examinations. Analyses correlated demographic, neurologic, and psychiatric features of CD patients with or without effective AM. Results: Of 154 people studied, 138 (89.6%) used AM, of which 60 (43.4%) reported partial improvement, 55 (39.8%) marked improvement, and 4 (0.03%) no effect on dystonic posture. Light touch, usually to the lower face or neck, was used by >90%. The presence or location of AM did not correlate with the severity of the dystonia. Conclusions: In this large and comprehensive study of CD, we found no clinical predictors of effective AM. Further studies of sensorimotor integration in dystonia are needed to better understand the pathophysiology of AM.